Behind Hartker's antiphoner Neglected fragments of the earliest Sankt Gallen tonary (Cambridge University Press, Cambridge, 2018)
Resumen: Prior to the famous Hartker Antiphoner (Sankt Gallen, Stiftsbibliothek, Cod. 390/391), copied in Sankt Gallen c. 1000, there survives no complete, fully notated witness to the Romano-Frankish chant repertory for the Office. Scholars have long known about the related tonary, possibly a decade older, in which the Sankt Gallen repertory is to be found ordered by melody. But unrecognised until now are the remains of a second tonary (Stadt-archiv Goslar, Handschriftenfragmente MThMu 1/1), datable to the early tenth century. The combined testimony of these two tonaries, together with other surviving fragments, is taken as the basis for a reassessment of the Office repertory in tenth-century Sankt Gallen. Nineteenth-century scholarshio gave Hartker's Antiphoner and arguably undeserved reputation as an authorised monument of Gregorian Chant. This view seems unsustainable in the light of many apparent editorial interventions, yet it may be precisely what the monks had set out to achieve.